Translating Audio Description Scripts Translation as a New Strategy of Creating Audio Description - Jankowska, Anna (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2015)
Translating audio description scripts from foreign into source language seems to be a tempting alternative strategy of creating audio description scripts in those countries where audio description is still scarce. This book presents the results of a three-stage study. This study was conducted to test whether the translation of audio description scripts written by experienced British audio describers into Polish is a solution that is less time and money consuming. Besides it was analysed whether the scripts created through the application of the translation strategy preserve the quality that satisfies the target recipients. The obtained results prove that translation of audio description scripts is not only possible, but also beneficial when it comes to time consumption, costs and quality of audio description